Scoring of the radiological picture of idiopathic interstitial pneumonia: a study to verify the reliability of the method. (3rd November 2015) - Kocova, Eva; Vanasek, Jiri; Koblizek, Vladimir; Novosad, Jakub; Elias, Pavel; Bartos, Vladimir; Sterclova, Martina
Background: Idiopathic pulmonary fibrosis (IPF) is a clinical form of usual interstitial pneumonia (UIP). Computed chest tomography (CT) has a fundamental role in the multidisciplinary diagnostics. However, it has not been verified if and how a subjective opinion of a radiologists or pneumologists can influence the assessment and overall diagnostic summary. Purpose: To verify the reliability of the scoring system. Material and Methods: Assessment of conformity of the radiological score of high-resolution CT (HRCT) of lungs in patients with IPF was performed by a group of radiologists and pneumologists. Personal data were blinded and the assessment was performed independently using the Dutka/Vasakova scoring system (modification of the Gay system). The final score of the single assessors was then evaluated by means of the paired Spearman's correlation and analysis of the principal components. Results: Two principal components explaining cumulatively a 62% or 73% variability of the assessment of the single assessors were extracted during the analysis. The groups did not differ both in terms of specialty and experience with the assessment of the HRCT findings. Conclusion: According to our study, scoring of a radiological image using the Dutka/Vasakova system is a reliable method in the hands of experienced radiologists. Significant differences occur during the assessment performed by pneumologists especially during the evaluation of the alveolar changes.